Developing Biofilm Resistant Catheter Coatings: Effect of Mimosa pudica L. Extract on Catheter-associated Urinary Tract Infections causing Agents (Asian Journal of Pharmaceutics (AJP), 2025)
Background: Among several nosocomial infections, catheter-associated urinary tract infection (CAUTI) is a very common one, and it often results in high morbidity as well as mortality, especially when the causative organisms are multidrug-resistant biofilm-forming pathogens. To prevent such biofilms and to make the treatment and management of the infection more effective, the scientific world is searching for novel antimicrobial catheter coating agents, and due to many factors, including multitarget actions, phytocompounds pose one of the promising options. Hence, our aim is to investigate the antibiofilm, antibacterial, and antiadhesive properties of a plant – Mimosa pudica L methanolic crude extract against major CAUTI-causing biofilm-forming microorganisms like Staphylococcus aureus, Enterococcus faecalis, Escherichia coli, and Candida albicans. Methods and Results: The crude extract showed potent antimicrobial activity against tested pathogens and also had excellent minimal inhibitory concentrations (MIC) as low as 0.312 mg/ml against all the tested microbes. The activity of antibiofilm was proved through crystal violet staining method, which revealed effective activity against all the test pathogens through biofilm inhibition and mature biofilm reduction. The antimicrobial activity of the catheter coated with M. pudica methanolic extract showed activity by growth inhibition around the catheter. In addition, M. pudica extract exhibited anti-oxidant property and also revealed no toxic effect to L929 cells. Conclusion: Based on these findings, the authors suggest detailed in vitro and in vivo investigations to develop M. pudica extract as a potential agent in treating and managing CAUTI.